Trade and Development Report 2021 - United Nations Conference on Trade; Development (United Nations, 2021)
This report analyses the state of the world economy, a year and half after the Covid-19 outbreak was declared a pandemic by the World Health Organization. The first part of the Report outlines key macro-financial aspects of the global economy, focusing, in particular, on the prospects for a growth recovery while analyzing possible threats from public and private debt, from inflationary spikes as well as from a return to the policies of the past. It pays particular attention to the situation of developing countries in the system of global finance, and discusses issues of debt sustainability. As this year marks its 40th anniversary, the Report also revisits the analyses provided in previous editions in response to shocks, setbacks, and crises that have hampered development during the era of hyperglobalization and underscores its abiding call for an inclusive global economic governance. The second part focuses on climate adaptation. It calls for a transformative approach to climate adaptation, with large-scale public investment programmes to adapt to future as well as current threats, and green industrial policies to drive growth and job creation. It also details reforms of the international financial system needed to get more climate adaptation funds flowing to developing countries.